Glutathione S-transferase activity in acetochlor, atrazine and oxyfluorfen metabolization in maize (Zea mays L.), sorghum (Sorghum bicolor L.) and wheat (Triticum aestivum L.) (Poaceae) - Cataneo, Ana Catarina [UNESP]; Chamma, Karina Luiz [UNESP]; Ferreira, Leonardo Cesar [UNESP]; Gomes Déstro, Guilherme Fernando [UNESP]; Carvalho, José Claudionir; Barbosa Novelli, Ethel Lourenzi [UNESP] (My University, 2002)
This experiment was conducted to evaluate the acetochlor, atrazine and oxyfluorfen herbicides plant selectivity, in relation to glutathione S-transferase activity (GST) in maize (Zea mays L.), sorghum (Sorghum bicolor L.) and wheat (Triticum aestivum L) (Poaceae) plants. GST activity was detected 24, 48 and 72 hours after treatment applications. The experiment's treatments consisted of spraying plants with water (control), acetochlor (3 L.ha -1), atrazine (4 L.ha -1) and oxyfluorfen (1 L.ha -1). The highest GST activities were observed in presence of acetochlor, mainly at 48 hours after treatment. These increments were 105, 148 and 118% when compared to maize, sorghum and wheat control groups, respectively. It is suggested that the GST may have a role in acetochlor degradation and it may be a reason for this herbicide's selectivity in these crops.
Keywords: Acetochlor; Atrazine; Glutathione S-transferase; Herbicides; Oxyfluorfen; Selectivity; acetochlor; atrazine; glutathione transferase; herbicide; oxyfluorfen; unclassified drug; water; aerosol; controlled study; degradation; evaluation; experiment; maize; nonhuman; plant; plant metabolism; Poaceae; reaction analysis; sorghum; sorghum bicolor; time; wheat; Sorghum bicolor; Triticum; Triticum aestivum; Zea; Zea mays